Development of the UTBK Try Out Application with Simulation Methods to Increase Student Scores - Saluky Saluky; Yoni Marine (ITEJ (Information Technology Engineering Journals), 2021)
Along with the rapid development of technology today, electronic devices have become commonplace for generation z. One of the uses of the current pandemic era is for learning activities. This computer-based test Tryout application was developed as a student learning tool to face the real exam. Using the simulation method, students can do UTBK tryouts repeatedly until they reach the minimum target requirements. This application is expected to provide convenience for students to know their abilities and can improve their knowledge. So that students can be better prepared for the exam.